Educação escolar indígena: a experiência dos Wapixana da aldeia Maruranau, Sul do Rupununi - Abraham, Felician Andre (2017)
The home of the Wapishanas (Arawaks) is the South Rupununi Region 9 comprised of 17 indigenous villages and has a population of 8,395 inhabitants. The development of this research occurred through the analysis of narratives of some residents from Maruranau village. Henceforth, the aim of the study seeks to comprehend the constitution process of formal education in the indigenous community from the villagers’ experiences of formal learning offered to them through their interviews which generated an understanding how they perceive formal education in their village. The first chapter deals with formal education in Guyana, from the colonial period to the present, emphasizing its modifications over the years and its introduction to the Wapishanas in the South Rupununi. The second chapter addresses historical aspects of location, population and general sociocultural observations of the Wapishanas. The third chapter relates from the field research the history of the school and community to present, also the experience of formal education among the Wapishanas and the responses they gave of the model of education which has been proposed to them.